The Impact of Jolly Phonics on the Vocabulary Achievement of Pupils in Primary Schools - Magdalene I. Ogbemudia; Victor M. Alasa (Jurnal Pendidikan Abad Ke-21, 2026)
The impact of Jolly Phonics on vocabulary accomplishment in elementary schools in the Uyo Local Government Area of Akwa Ibom State, Nigeria, was examined in this study. The vocabulary achievement scores of students who were taught reading skills using Jolly Phonics and those who were not, the vocabulary achievement scores of students who were taught spelling skills using Jolly Phonics and those who were not, and the vocabulary achievement scores of students who were taught writing skills using Jolly Phonics and those who were taught without Jolly Phonics in the Local Government Area were all considered in this study. With a non-randomized pretest-posttest control group and a sample size of 120 participants, the study used a quasi-experimental methodology.The data was analyzed using the mean, standard deviation, and Analysis of Variance (ANOVA). In primary schools in the Uyo Local Government Area of Akwa Ibom State, Nigeria, there was a significant difference in vocabulary achievement scores between students taught reading skills using Jolly Phonics and those taught without it, between students taught spelling skills using Jolly Phonics and those taught without it, and between students taught writing skills using Jolly Phonics and those taught without it, according to the study's findings at the 0.5 level of significance. Recommendations were provided when needed.